Near-infrared downconversion luminescence of SrMoO4:Tm3+, Yb3+ phosphors. (September 2017) - Li, Li; Pan, Yu; Chang, Wenxuan; Feng, Zhongshan; Chen, Peng; Li, Chen; Zeng, Ziyu; Zhou, Xianju
Graphical abstract: The calculated band structure of SrMoO4 and the visible and infrared emission spectra of SrMoO4 :1%Tm 3+, 10%Yb 3+ phosphors under 283 nm excitation. Highlights: Near-infrared downconversion luminescence of SrMoO4 :Tm 3+, Yb 3+ phosphors were systematically investigated. The electronic structure of SrMoO4 was estimated by density functional theory. The quenching concentration of Yb 3+ ions approaches 10 mol%. The energy transfer mechanism was discussed in detail. Abstract: Tm 3+ and Yb 3+ codoped SrMoO4 phosphors were synthesized by the high-temperature solid-state reaction method. The structure, ultraviolet-visible diffuse reflectance spectra, photoluminescence, decay properties and theoretical energy transfer efficiency of the phosphors were investigated in detail. The electronic structure and band gap of SrMoO4 were estimated by density functional theory (DFT) calculation. The XRD results show that all the prepared phosphors can be readily indexed to scheelite-type structure. The strong visible emission around 473 nm from Tm 3+ ( 1 G4 → 3 H6 ) and near-infrared (NIR) emission around 998 nm from Yb 3+ ( 2 F5/2 → 2 F7/2 ) of the SrMoO4 :Tm 3+, Yb 3+ phosphors were observed under 283 nm excitation. The dependence of the visible and NIR emissions on Yb 3+ concentration have also been investigated. The quenching concentration of Yb 3+ ions approaches 10 mol%. In addition, the energy transfer processes and possible transfer routes were proposed.